2016
DOI: 10.3389/fmicb.2016.02052
|View full text |Cite|
|
Sign up to set email alerts
|

Cinnamaldehyde Inhibits Staphylococcus aureus Virulence Factors and Protects against Infection in a Galleria mellonella Model

Abstract: Bacterial resistance to the available marketed drugs has prompted the search of novel therapies; especially in regards of anti-virulence strategies that aim to make bacteria less pathogenic and/or decrease their probability to become resistant to therapy. Cinnamaldehyde is widely known for its antibacterial properties through mechanisms that include the interaction of this compound with bacterial cell walls. However, only a handful of studies have addressed its effects on bacterial virulence, especially when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
52
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 52 publications
15
52
3
1
Order By: Relevance
“…Our results are similar to those obtained by Ferro et al [22], who also found that 1/2 MIC of TC reduced S. aureus metabolic activity in biofilm. In our study, reduction of metabolic activity in the presence of TC at 1/2 MBIC reached over 50%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are similar to those obtained by Ferro et al [22], who also found that 1/2 MIC of TC reduced S. aureus metabolic activity in biofilm. In our study, reduction of metabolic activity in the presence of TC at 1/2 MBIC reached over 50%.…”
Section: Discussionsupporting
confidence: 93%
“…Variability between clinical isolates was also observed in other studies-MIC of TC for S. epidermidis isolates were 400-500 µg/mL [29]. Other research concerning antimicrobial activity of TC showed that MIC values for S. aureus isolates were higher than in our study (250 µg/mL) [22]. These results support our findings, showing diversity in the sensitivity on TC within the species.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another phytochemical, namely cinnamaldehyde, the predominant active compound found in cinnamon oil from the stem bark of the Cinnamomum cassia, was found not to induce any toxicity and enhanced the survival rate of larvae when they when infected by S. aureus ATCC 25923. Moreover, cinnamaldehyde significantly reduced the number of bacteria in larvae hemolymph in comparison with that in those in the untreated groups [77].…”
Section: Staphylococcus Aureus (Saureus)mentioning
confidence: 84%
“…Extracts and EOs of C. zeylanicum exhibit significant antimicrobial activities against several organisms, including the fungus Aspergillus (GOMEZ et al, 2018), M. tuberculosis (MOTA et al, 2018), gram-positive bacteria, (WIWATTANARATTANABUT et al, 2017), and gram-negative bacteria (LIU et al, 2017). The antibacterial activity of TCin has also been evaluated against several gram-negative bacteria (UTCHARIYAKIAT et al, 2016), gram-positive bacteria, (FERRO et al, 2016), and H37Rv strain of M. tuberculosis (ANDRADE-OCHOA et al, 2015;POLAQUINI et al, 2017). However, the antimycobacterial activities of CzeyEO and TCin have not been assessed against sensitive and resistant clinical isolates of M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%